2018
DOI: 10.1136/bmjdrc-2018-000525
|View full text |Cite
|
Sign up to set email alerts
|

Need to improve awareness and treatment compliance in high-risk patients for diabetic complications in Nepal

Abstract: Objective/introductionIt is known that knowledge, awareness, and practice influence diabetic control. We compared factors pertaining to healthy lifestyle (exercising, avoiding smoking), self-help (attending appointments, following treatment regimens), and diabetic awareness in high-risk patients for diabetic complications, specifically, those on insulin versus non-insulin treatment, and also those with a longer diabetic duration (≥5 years) versus a shorter duration.Methods200 consecutive patients with type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…It is well known that the control of diabetes is important for reducing the risk of sight-threatening DR (STDR), as suggested by several studies including the UK Prospective Diabetes Study and Diabetic Retinopathy Clinical Research 11–14. The role of self-help (taking medicine in time, not missing doctor’s appointments, monitoring blood sugar levels regularly)15 and improved awareness about diabetes in controlling sight-threatening complications of DR is less well documented. There is evidence in the literature to suggest that improving diabetic self-help, or knowledge/awareness about diabetes and its risk factors, plays an important role in the control of diabetes and DR 15–18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the control of diabetes is important for reducing the risk of sight-threatening DR (STDR), as suggested by several studies including the UK Prospective Diabetes Study and Diabetic Retinopathy Clinical Research 11–14. The role of self-help (taking medicine in time, not missing doctor’s appointments, monitoring blood sugar levels regularly)15 and improved awareness about diabetes in controlling sight-threatening complications of DR is less well documented. There is evidence in the literature to suggest that improving diabetic self-help, or knowledge/awareness about diabetes and its risk factors, plays an important role in the control of diabetes and DR 15–18.…”
Section: Introductionmentioning
confidence: 99%
“…The role of self-help (taking medicine in time, not missing doctor’s appointments, monitoring blood sugar levels regularly)15 and improved awareness about diabetes in controlling sight-threatening complications of DR is less well documented. There is evidence in the literature to suggest that improving diabetic self-help, or knowledge/awareness about diabetes and its risk factors, plays an important role in the control of diabetes and DR 15–18. A recent Cochrane review of 66 randomised clinical trials highlights the fact that interventions in the form of educational programmes to increase awareness about DR is vital in improving attendance for DR screening; more specifically, interventions provided in the form of education, reminders and promotion of self-care targeting patients, healthcare professionals or the healthcare system, were found to improve attendance for DR screening by 12% 19…”
Section: Introductionmentioning
confidence: 99%
“…In this proposed community-based intervention, the changes in the HbA1c levels (continuous outcome) was considered for calculating the sample size for the individuals with diabetes and the incidence of diabetes (binary outcome) was considered for calculating the sample size for the individuals with prediabetes respectively. For the individuals with diabetes, we aim to detect a clinically significant reduction in HbA1c levels from 7.6% to 6.5% (SD=1.5%) (based on our assumption, recommended effective diabetic management level, and results of previous studies) among the individuals with diabetes during the 12 months period [35,36] with medium effect size [37]. We expect a reduction of HbA1c to 7.0% in the control group, an optimal target level defined by American Diabetes Association (ADA) [38].…”
Section: Sample Sizementioning
confidence: 99%
“…Amongst the diabetic population in Nepal, 8% -18% are on insulin [5] [6]. In a prospective study assessing the drug prescribing trend in 100 patients including 41 diabetic patients, insulin was included only in 2.5% of prescriptions [7].…”
Section: Rising Burden Of T2dm In Nepalmentioning
confidence: 99%
“…In a prospective study assessing the drug prescribing trend in 100 patients including 41 diabetic patients, insulin was included only in 2.5% of prescriptions [7]. In a study conducted by Sapkota et al in 200 diabetic patients, 52% patients self-reported not knowing whether their diabetes was well-controlled and 42% had to seek help at least once within the last year for uncontrolled diabetes (in-Open Journal of Endocrine and Metabolic Diseases cluding hypo or hyperglycemia) [6]. The situation indicates towards potential for improving diabetes management by enhancing insulin utilization in Nepalese diabetic patients.…”
Section: Rising Burden Of T2dm In Nepalmentioning
confidence: 99%